Loss/Down-Regulation of Tumor Suppressor in Lung Cancer 1 Expression Is Associated With Tumor Progression and Is a Biomarker of Poor Prognosis in Ovarian Carcinoma. Issue 3 (1st April 2011) - Yang, Guofen; He, Weipeng; Cai, Muyan; Luo, Fei; Kung, Hsiangfu; Guan, Xinyuan; Zeng, Yixin; Xie, Dan
Abstract : Objectives: The tumor suppressor in lung cancer 1 (TSLC1) has been identified as a putative tumor suppressor gene in non-small cell lung cancer. Although loss of TSLC1 has been observed in a number of human malignancies, the expression levels of TSLC1 gene in ovarian cancer and its clinical or prognostic significance have not been investigated. Methods: Protein expression levels of TSLC1 was explored by semiquantitative immunohistochemical staining on archival formalin-fixed, paraffin-embedded pathological specimen consisting of 30 normal ovaries, 30 ovarian cystadenomas, 40 borderline ovarian tumors, and 160 invasive ovarian carcinomas. The TSLC1 immunohistochemical staining results were then correlated with various clinicopathologic parameters and patient prognosis using various statistical models. Results: Significantly decreased, or complete loss of, protein expression of the TSLC1 gene was observed in 59% ovarian carcinomas, 45% borderline tumors, and 7% cystadenomas, but in none of the normal ovaries (0%). In ovarian carcinomas, decreased TSLC1 expression was significantly correlated with lymph node metastasis (pN, P = 0.001), distant metastasis (pM, P = 0.028), and more advanced International Federation of Gynecology and Obstetrics stages ( P = 0.008). By univariate survival analysis on the ovarian carcinoma cohorts, decreased TSLC1 protein expression was significantly associated with shortened patient survival (mean: 26.9 months in tumors with complete loss of TSLC1 vs 63.1 months in tumors with significantly decreased TSLC1 vs 94.3 months in tumors with normal levels of TSLC1; P < 0.001). By multivariate analysis, TSLC1 protein expression remained as a significant and independent prognostic factor for the prediction of patient survival ( P = 0.003). Conclusions: Decreased protein expression of the TSLC1 gene might be important in conferring a more aggressive behavior in ovarian carcinoma. Thus, TSLC1 may be used as an independent prognostic molecular marker for patients with ovarian carcinoma.